The impact of lipocalin-type-prostaglandin-D-synthase as a predictor of kidney disease in patients with type 2 diabetes - Bacci MR; Cavallari MR; de Rozier-Alves RM; Alves BCA; Fonseca FLA (Dove Medical Press, 2015)
Marcelo Rodrigues Bacci1, Marina Romera Cavallari1, Ross Martin de Rozier-Alves2, Beatriz da Costa Aguiar Alves2, Fernando Luiz Affonso Fonseca2,31General Practice Department, 2Clinical Analysis Laboratory, ABC Medical School, 3Biological Sciences Department, Federal University of São Paulo, São Paulo, BrazilAbstract: Hypertension and diabetes are clinical conditions which contribute to the development of chronic kidney disease as well as risk factors for cardiovascular events. In recent years, lipocalin-type-prostaglandin-D-synthase (beta trace protein; BTP) has increasingly been studied as an alternative to creatinine for the evaluation of renal function as well as for being a possible biomarker for cardiovascular disease. It is expected that the levels of BTP in patients with cardiovascular disease are elevated, as is the case with patients with renal dysfunction. The objective of this study is to realize a systematic review of the pertinent literature in respect to BTP as a biomarker of renal dysfunction in diabetic patients. Using the database MEDLINE, a search up to year 2014 was conducted using the follow descriptors: “lipocalin type prostaglandin d synthase” AND “diabetes”; “lipocalin type prostaglandin d synthase” and “diabetic nephropathy”; “beta trace protein” AND “diabetes”; “beta trace protein” AND “diabetic nephropathy”. The criteria used for inclusion were the presence of the referring to terms in title or abstract and study conducted in humans. About 17 articles were selected, of which six articles were duplicates, and of which six articles did not investigate any possible relationship between the protein (BTP) and either diabetes or nephropathy. The final result yielded five articles to be analyzed. This review found BTP is not influenced by race, by body mass index nor by patient’s sex. BTP can be considered as a reliable early biomarker of renal dysfunction in diabetics. BTP is associated with metabolic syndrome and is also associated with greater cardiovascular risk. Prospective data establishing a correlation between BTP and mortality would have been of great interest, but such articles were not found in this review.Keywords: renal lesions, type 2 diabetes, lipocalin-type-prostaglandin-D-synthase, diabetes predictor